PEMANFAATAN MEDIA SOSIAL (YOUTUBE) SEBAGAI MEDIA PENYAJIAN KREASI DALAM PEMBELAJARAN - Irfan Ripandy, - (2022)
UTILIZATION OF SOCIAL MEDIA (YOUTUBE) AS A CREATIVE PRESENTATION MEDIA IN LEARNING The purpose of the study was to determine the use of social media (Youtube) as a medium for presenting artistic creations in learning. This study uses qualitative research with a phenomenological approach. This research was conducted by interview using a questionnaire to the fourth grade teacher resource persons at primary school Sinarjati III. This data collection technique uses interview techniques as well as documentation and observation. This research is based on the results of interviews. In its application, videos on Youtube can also be seen as good Audio Visual media. In addition to displaying Youtube images, it can also be used in learning because students can observe the correct dance movement material (covering all limb movements) the correct expression (happy happy, sad and romantic). In utilizing the Youtube application as a medium for presenting art creations in learning. Many teachers use several features including the Subtitle feature, namely the language translator feature that can be used on videos, the description feature to find out the description of the video title that matches the material, which is useful as a grouping according to the theme to be used. The live streaming feature is a live feature that can be seen by anyone including students with the convenience of students only needing to type the keywords on Youtube as an Up-to-date medium where fast-paced information can be easily obtained on social media including Youtube. Lack of many shows that are not suitable for children. Keywords: Youtube, Application, Utilization